Genetic homogeneity among Ugandan isolates of Xanthomonas campestris pv. musacearum revealed by randomly amplified polymorphic DNA analysis - Odipio, J.; Tusiime, Geoffrey; Tripathi, L.; Aritua, Valentine (2009)
The Random Amplification of Polymorphic DNA (RAPD) analysis was used to detect the genetic diversity among Ugandan isolates of Xanthomonas campestris pv. musacearum (Xcm), the causal agent of banana Xanthomonas wilt (BXW) disease. Seven random primers were used because of their ability to amplify reproducible and reliable fingerprints generated between 6 - 12 amplicons each from the Xcm isolates obtained from central core of pseudostems, peduncles, fruit peelings, sap, nectar,insects’ bodies and bacterial oozes. Regardless of the source and geographical origin, similar fingerprints were generated from the tested isolates. Using a similarity coefficient of 58%, the unweighted pair group method with arithmetic averaging (UPGMA) analysis did not reveal any significant differences in clustering, with exception of a single isolate that had unique fingerprints. Prior to the genetic analysis, all the isolates compared showed no significant difference (P = 0.92) with regard to incubation period for appearance of symptoms and the severity of symptoms in pathogenicity test. Thus, our data indicates that the population of Xcm in Uganda is clonal, that is, one uniform population being spread fast and efficiently, suggesting that there is a low likelihood of the current population to rapidly evolve, in the near future, into more virulent strains to overcome any resistance deployed.